The Effect of Diaphragm Therapy on Comfort in COPD Patients in The Cempaka Pavilion, Jombang Hospital - Agustina Maunaturrohmah; Endang Yuswatiningsih (Alliance oh Health Activists (AloHA), 2019)
Patients who experience shortness of breath will cause discomfort in body function and limited independence, so patients tend to avoid daily physical activities that cause immobilization, the relationship of patients with the social environment decreases. The aim of this study was to analyze the effect of diaphragm therapy on the comfort of patients with chronic obstructive pulmonary disease (COPD). The design of this study was one group pre-post test. The population were all patients in the Cempaka pavilion at Jombang Hospital with an average of 26 patients per month. The sample size were 20 respondents, selected using simple random sampling technique. Data were collected using questionnaire, then analyzed using Paired Sample T Test. The results showed that before being given diaphragm therapy, 13 respondents (65%) felt uncomfortable and after giving diaphragm therapy, 14 respondents (70%) felt comfortable. Statistical test results with Paired Sample T Test obtained pvalue of 0.035. Conclusion: there is an effect of diaphragm therapy on comfort in patients with COPD. Keywords: diaphragm therapy; comfort; COPD